Tension-after-impact analysis and damage mechanism evaluation in laminated composites using AE monitoring. (1st March 2023) - Hoseinlaghab, S.; Farahani, M.; Safarabadi, M.; Nikkhah, M.
Graphical abstract: Highlights: Four dominant damage mechanisms in tensile loading of GFRPs were detected using AE. The peak frequency range of each damage mechanism was determined. The share of each damage mechanism in composite failure was calculated by wavelet transform. The AE results verified using SEM images. The effects of nanoparticles on the LVI and TAI strength of GFRPs had been investigated. Abstract: The present paper focuses on the detection of dominant damage mechanisms in tensile loading of laminated composite specimens subjected to low-velocity impact (LVI) using acoustic emission (AE) method. Moreover, the effects of various nanoparticles (NPs) on the tension-after-impact (TAI) strength of glass fiber-reinforced polymer (GFRP) composites have been investigated. The hierarchical method was employed to cluster the acoustic emission data and detect the damage mechanisms of the composites. These damage are matrix cracking, fiber–matrix debonding, fiber breakage, and fiber pull-out, the peak frequency ranges of which were obtained to be (100–200), (250–370), (410–530), and (570–650) kHz, respectively. Subsequently, the existence of these mechanisms was verified using Scanning Electron Microscope (SEM) images, and their shares in composite failure under tensile loading were calculated by wavelet transform method. According to the results, the NPs have enhanced the impact strength of the GFRPs by up to 66% reduction in damage index. Furthermore, they have increased TAI strength by up to 39%, claims also supported by the AE analysis.